Resilience mediates the relationship between household dysfunction in childhood and postpartum depression in adolescent mothers in Peru - Carroll, Haley (2021)
Postpartum depression is related to a variety of adverse health outcomes for mothers and children [[1], [2], [3]]. Of particular concern, when compared to older mothers, being an adolescent mother is associated with an assortment of risks that precede the pregnancy, such as adverse experiences in childhood, as well as risks that occur together with raising the child, such as experiencing postpartum depression [[2], [3], [4], [5]]. Children of mothers with postpartum depression are more likely to have a constellation of adverse outcomes including lower infant birth weight, lower child growth, increased risk for childhood obesity, as well as adverse neurodevelopmental and behavioral outcomes [6,7] that may persist into childhood [8] and increase the risk for childhood mental health disorders [9]. Moreover, estimates in low and middle income countries suggest up to 25% of pregnant women experience symptoms of common mental health disorders including depression [6]. Thus, adolescent mothers in low and middle income countries are particularly vulnerable to pregnancy related complications, as maternal and reproductive health problems are a key cause of disease burden